2012
DOI: 10.1016/j.coi.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis and function of regulatory T cells in aging

Abstract: A hallmark of aging is the progressive deterioration of immune function. Age-related immune suppression increases susceptibility to infectious diseases and cancer, significant causes of morbidity and mortality in the elderly. In particular, age-related T cell dysfunction is a major contributor to “immune-senescence”. Recently, it has become clear that the frequency of regulatory T cells (Treg) significantly increases in aged mice and humans. As Treg control the intensity of T cell responses, their accrual like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 51 publications
9
109
1
2
Order By: Relevance
“…Importantly, we distinguished CD45RA+CD25 int nTreg and CD45RA-CD25 high memT reg cells according to a state of the art flow cytometric gating strategy (Miyara et al, 2009) and confirmed their expression of the Treg transcription factor FOXP3, as well as their suppressive potential in vitro (Miyara et al, 2009;Booth et al, 2010). In earlier studies, aging was associated with either an increase or no change of circulating T reg cells (Raynor et al, 2012). Notable, a multitude of gating strategies was applied to identify T reg cells in earlier studies, without discriminating between nT reg and memT reg cells.…”
Section: Discussionmentioning
confidence: 55%
“…Importantly, we distinguished CD45RA+CD25 int nTreg and CD45RA-CD25 high memT reg cells according to a state of the art flow cytometric gating strategy (Miyara et al, 2009) and confirmed their expression of the Treg transcription factor FOXP3, as well as their suppressive potential in vitro (Miyara et al, 2009;Booth et al, 2010). In earlier studies, aging was associated with either an increase or no change of circulating T reg cells (Raynor et al, 2012). Notable, a multitude of gating strategies was applied to identify T reg cells in earlier studies, without discriminating between nT reg and memT reg cells.…”
Section: Discussionmentioning
confidence: 55%
“…Aging has been associated with dysregulation of the immune system, which is then unable to fully respond to pathological insults (Plackett et al, 2004;Raynor et al, 2012). We thus evaluated how aging and chronic systemic infection influenced the concentrations of inflammatory cytokines and chemokines in both plasma and brain.…”
Section: Concentrations Of Plasma Cytokines Increase Within Hours Aftmentioning
confidence: 99%
“…[5][6][7] Despite permanent thymic emigration in the young or in the face of thymus involution during aging, the peripheral frequencies of Treg cells are physiologically kept stable throughout the majority of a lifetime, with significant increases being observed only in aged mice and humans. [8][9][10][11] This homeostatic balance implies a competition between recently thymus-emigrated (RTE) natural Treg cells and those Treg cell clones already resident in the periphery, which are generated by clonal expansion of natural Treg cells and/or post-thymic conversion to Treg phenotype, originating the so-called peripherally induced Treg.…”
Section: Cd4mentioning
confidence: 99%